2019
DOI: 10.1029/2019ja026731
|View full text |Cite
|
Sign up to set email alerts
|

An Extended MHD Study of the 16 October 2015 MMS Diffusion Region Crossing

Abstract: The Magnetospheric Multiscale (MMS) mission has given us unprecedented access to high cadence particle and field data of magnetic reconnection at Earth's magnetopause. MMS first passed very near an X‐line on 16 October 2015, the Burch event, and has since observed multiple X‐line crossings. Subsequent 3‐D particle‐in‐cell (PIC) modeling efforts of and comparison with the Burch event have revealed a host of novel physical insights concerning magnetic reconnection, turbulence‐induced particle mixing, and seconda… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
(99 reference statements)
1
11
0
Order By: Relevance
“…[32][33][34] In the magnetosphere, the LHDI may drive turbulence during magnetopause reconnection, 35,36 and can quicken the onset of reconnection in regimes relevant to magnetotail reconnection. 37,38 Prior studies of the LHDI using the ten-moment model show that it is important to retain the ion kinetic effects using the nonlocal closure, 19,20 and we find the heat flux closure in this work is able to reproduce the growth of the LHDI in a current sheet.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…[32][33][34] In the magnetosphere, the LHDI may drive turbulence during magnetopause reconnection, 35,36 and can quicken the onset of reconnection in regimes relevant to magnetotail reconnection. 37,38 Prior studies of the LHDI using the ten-moment model show that it is important to retain the ion kinetic effects using the nonlocal closure, 19,20 and we find the heat flux closure in this work is able to reproduce the growth of the LHDI in a current sheet.…”
Section: Introductionmentioning
confidence: 59%
“…We have also been able to simulate the lower-hybrid drift instability in a current sheet with the ten-moment model, which was previously only possible when using a nonlocal closure or tuning the model parameters carefully. 19 To date, the only large-scale simulations performed using the ten-moment model have used local relaxation of the pressure tensor, 20,22,23 with some success in comparison to observations. The closure used in this paper, while having larger computational costs, shows better agreement with kinetic simulations, particularly for the reconnection and instability physics being investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed agreement with MMS data for kinetic particle-in-cell (PIC) simulations (e.g. Nakamura et al 2018a) and for 10-moment fluid simulations (TenBarge et al 2019). Both models retain the anisotropic pressure tensor which is one mechanism to break the frozen-in condition in collisionless reconnection (Egedal et al 2019).…”
Section: Introductionmentioning
confidence: 64%